A Participatory Generation? The Generational and Social Class Bases of Political Activism in Turkey - Inan, Murat; Grasso, Maria T. (Routledge Journals, Taylor & Francis Ltd, 2017)
This research aims to understand the extent to which generation and social class determine Turkish respondents' level of political activism. It tests both the macroeconomic socialization effect and the social class effect on political activism as hypothesized by Inglehart and Lipset, respectively. It also strives to understand whether a macropolitical period effect may also some generational implications for political activism. Beyond these examinations, it also raises a challenge to Lipset's working-class authoritarianism thesis - within the particular area of political activism - for those generations which came of age under an authoritarian politico-juridical order as well as for those which did not.
Keywords: Political Activism; Generation Effects; Socialization; Social Class; World Values Survey; Turkish Politics